2020
DOI: 10.1371/journal.pntd.0008115
|View full text |Cite
|
Sign up to set email alerts
|

Deep phosphoproteome analysis of Schistosoma mansoni leads development of a kinomic array that highlights sex-biased differences in adult worm protein phosphorylation

Abstract: Although helminth parasites cause enormous suffering worldwide we know little of how protein phosphorylation, one of the most important post-translational modifications used for molecular signalling, regulates their homeostasis and function. This is particularly the case for schistosomes. Herein, we report a deep phosphoproteome exploration of adult Schistosoma mansoni, providing one of the richest phosphoprotein resources for any parasite so far, and employ the data to build the first parasite-specific kinomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 108 publications
1
31
0
Order By: Relevance
“…Recently, drugs acting on phosphorylation and protein kinases have been proposed as novel targets for schistosomiasis treatment [25,26,[55][56][57]. Kinomic array of S. mansoni revealed a number of kinases those are vital for Schistosoma biology [31] in which Src kinase, Cyclin-dependent kinase (CDK), PKC were predicted from bioinformatic tool as the critical kinases for anthelminthic effects of PZQ (Table S3). Our study indicates that kinases of critical pathways in the parasite and Src kinase are important kinases for PZQ response ( Figure S1, Table S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, drugs acting on phosphorylation and protein kinases have been proposed as novel targets for schistosomiasis treatment [25,26,[55][56][57]. Kinomic array of S. mansoni revealed a number of kinases those are vital for Schistosoma biology [31] in which Src kinase, Cyclin-dependent kinase (CDK), PKC were predicted from bioinformatic tool as the critical kinases for anthelminthic effects of PZQ (Table S3). Our study indicates that kinases of critical pathways in the parasite and Src kinase are important kinases for PZQ response ( Figure S1, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-phosphoserine was used to determine phosphorylation levels and tissue localization in the parasites. In Schistosoma parasite, the main phosphorylated residues are serine (67.8%), threonine (20.1%) and tyrosine (12.1%) [31]. Phosphorylation of tegument, muscle and internal cells of the worms were markedly reduced after PZQ treatment, as indicated by the black spots in Figure 3.…”
Section: Effects Of Pzq On S Mekongi Phosphorylation and Phosphoprotmentioning
confidence: 95%
“…Therefore, applying Src kinase inhibitors could be a novel approach to treat Mekong schistosomiasis. In another study on S. mansoni , the phosphoproteome of S. mansoni was first comprehensively analyzed based on a novel peptide kinomic array, which has characterized 12936 phosphorylation sites in 3176 proteins ( Hirst et al., 2020 ). The phosphorylation sites identified from S. mansoni cover a wider area than these identified from S. japonicum .…”
Section: Phosphoproteomics Reveals the Important Role Of Pks In S Japonicummentioning
confidence: 99%
“…The phosphorylation sites identified from S. mansoni cover a wider area than these identified from S. japonicum . It was also shown that many PKs such as CaMKII, PKA and CK1/2 are of great importance to schistosome function ( Hirst et al., 2020 ). Interestingly, the distribution of phosphorylations among serine, threonine, and tyrosine is 68%:20%:12% in S. mansoni , and a greater proportion (3 to 4-fold) of phosphotyrosine is determined compared to other organisms ( Rigbolt et al., 2011 ; Lasonder et al., 2012 ).…”
Section: Phosphoproteomics Reveals the Important Role Of Pks In S Japonicummentioning
confidence: 99%
See 1 more Smart Citation